2013
DOI: 10.1080/09500693.2013.775610
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socio-environmental Projects of Jewish and Bedouin Youth in Israel on Students’ Local Knowledge and Views of Each Other

Abstract: This study is part of a first study of collaborative socio-environmental projects that engage Jewish and Arab students in Israel in learning about their local environment and about each other through outdoor learning and environmental action. We used ideas of social learning and environmental citizenship to frame our research. We investigated students' knowledge regarding their local environment and their knowledge of each other's community. We also studied the participants' views regarding their project-partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…It is reinforced by Brody () who viewed activity as central to learning in the outdoors, and by Ballantyne and Packer () who found that most engaging, effective and enduring learning experiences in natural environments occur through experience based rather than teacher‐directed strategies. It is supported as well by our own study of extended outdoor education programs in multicultural contexts (Alkaher & Tal, ; Morag, Tal, & Keren‐Rotem, ). Some of these studies were informed by the sociocultural theory and others by a few theoretical strands.…”
Section: Discussionsupporting
confidence: 55%
“…It is reinforced by Brody () who viewed activity as central to learning in the outdoors, and by Ballantyne and Packer () who found that most engaging, effective and enduring learning experiences in natural environments occur through experience based rather than teacher‐directed strategies. It is supported as well by our own study of extended outdoor education programs in multicultural contexts (Alkaher & Tal, ; Morag, Tal, & Keren‐Rotem, ). Some of these studies were informed by the sociocultural theory and others by a few theoretical strands.…”
Section: Discussionsupporting
confidence: 55%
“…As I have already acknowledged, I strongly believe in the power of informal experiences with science and in a variety of forms of engagement with science. About a decade ago, we carried out two extended collaborative environmental projects involving Jewish and Arab high school students (Alkaher & Tal, 2014;Tal & Alkaher, 2010). In these projects, student groups together investigated local conflicts over land use between Arab villages and nature parks, and they initiated activist efforts to protect nature while addressing local needs.…”
Section: Prior Researchmentioning
confidence: 99%
“…Despite the educational program's benefits, it also highlighted several challenges for multicultural encounters, such as differences in teaching approaches and learning styles between the two cultural groups, as well as difficulties in communication due to language and cultural barriers. Despite such obstacles, the study revealed that beyond increasing the participants' awareness and willingness to protect the environment, all the participants acknowledged that the program enhanced intercultural understanding and acceptance, which decreased mutual prejudice [41,42].…”
Section: Multiculturalism and Multicultural Environmental Educationmentioning
confidence: 94%
“…It is reasonable to assume that such challenges are not unique to the Canadian context. Another example explored a MEE program implemented in Israel, that brought together Israeli Jewish and Arab (Bedouin) youth to learn collaboratively around environment projects aimed at protecting natural landscapes [41], focusing on the educators' and well as the learners' perspectives. Despite the educational program's benefits, it also highlighted several challenges for multicultural encounters, such as differences in teaching approaches and learning styles between the two cultural groups, as well as difficulties in communication due to language and cultural barriers.…”
Section: Multiculturalism and Multicultural Environmental Educationmentioning
confidence: 99%